2007
DOI: 10.1177/0883073807302757
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report of Neonatal Convulsions Due to Maternal Herpes Gestationis

Abstract: Herpes gestationis is a rarely seen autoimmune vesiculobullous and pruritic dermatosis of pregnancy. Neonatal morbidity associated with maternal herpes gestationis is controversial. The authors report the first case of neonatal convulsion with abnormal electroencephalography findings and transient vesicular eruption due to maternal herpes gestationis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
1
0
2
Order By: Relevance
“…Associations with small-for-gestational age weight at birth and preterm delivery (20%) have been reported [105], as well as a borderline increase in spontaneous abortions [71]. A case of fetal cerebral hemorrhage and a case of neonatal convulsions associated with HG in the neonate have been reported [106]. A recent study indicated that early onset of HG and blister formation are associated with adverse pregnancy outcomes [107].…”
Section: Complicationsmentioning
confidence: 99%
“…Associations with small-for-gestational age weight at birth and preterm delivery (20%) have been reported [105], as well as a borderline increase in spontaneous abortions [71]. A case of fetal cerebral hemorrhage and a case of neonatal convulsions associated with HG in the neonate have been reported [106]. A recent study indicated that early onset of HG and blister formation are associated with adverse pregnancy outcomes [107].…”
Section: Complicationsmentioning
confidence: 99%
“…Molar gebelik ve koryokarsinomla ilişkili olgular da bildirilmiştir (1)(2)(3)(4)(5)(6)8,9). Yenidoğanın %10'u aktif hastalık belirtileri gösterebilir.…”
Section: Introductionunclassified
“…GP tanısı için altın standart DİF' tir (2,3,8). Olgumuzda gözlediğimiz gibi, DİF incelemede, perilezyonal deride bazal membranda lineer C3 (%100) ve bazen IgG (%30-40) depolanması gözlenir (2)(3)(4)9).…”
Section: Introductionunclassified